Trace mineral status of buffaloes (Bubalus bubalis) from North-West Himalayan region in relation to fodder levels - SINGH, R; SHARMA, N; BHARDWAJ, R K; HUSSAIN, K (The Indian Journal of Animal Sciences, 2018)
To know the status of trace minerals in buffaloes from various agro-climatic zones of Jammu division, a baseline survey was conducted. A total of 193 buffalo blood and 169 fodder samples offered during various seasons were collected and analyzed. The average values of Cu, Zn, Fe, Mn and Co in buffalo plasma samples were 14.86, 31.27, 56.05, 1.98 and 3.35 Î¼mol/l, respectively. Sub-clinical deficiency of Cu, Zn, Fe and Mn was recorded among 34.42, 3.22, 7.05 and 11.97% buffalo population. Fodder sample analysis revealed wide variation in the level of trace elements among different fodders and also areas. Level of iron in fodders was adequate; however, Cu deficiency was prevalent among corn stover (55.55%), fodder tree leaves (50%) and Pennisatum typhoides (22.22%). Zn deficiency was recorded among Sorgum spp. (68.75%), corn stover (66.66%), wheat straw (82.5%), Pennisatum typhoides (37.5%), tree leaves (33.33%) and Trifolium alexandrium (15.38%). Mn deficiency was recorded among Sorgum spp. (62.5%), corn stover (66.66%), wheat straw (30.76%) and Pennisatum typhoides (44.44%). Study concluded that area specific mineral mixtures need to be supplemented for enhancing the productive and reproductive potential of buffaloes.